INTEGRASI ELEMEN RUANG PENENTU KEBERHASILAN TAMAN PUBLIK SEBAGAI RUANG KREATIF - Demami, Aliviana; Refranisa; Findanavy Ridzqo, Intan; Winangun, Dyah Khoirunnisa; Maulana, Rizki; Salam, Alva Antavas (Fakultas Teknik Universitas Tunas Pembangunan Surakarta, 2026)
The relationship between public space design and the creative industry ecosystem requires a multidisciplinary approach that considers physical, visual, social, and user experience dimensions. This study analyzes the integration of outdoor spatial elements in Taman Literasi Martha Christina Tiahahu as a case study to understand the role of public space in supporting urban creative activities. A descriptive-qualitative method was employed, involving field observation, spatial mapping, and thematic analysis based on public space design principles. The findings reveal that the synergy between physical elements, visual identity, and patterns of social interaction is a key determinant of the park’s success as a creative space. The analysis also highlights gaps between the existing design and community needs, particularly regarding the provision of collaborative spaces and noise management. This study contributes to the discourse on creative placemaking in Indonesia and proposes a holistic evaluative framework for assessing the quality of thematic public spaces in metropolitan contexts.